Design of low-profile transmitarray antennas with wide mechanical beam steering at millimeter waves - Vaquero, Á. F.; Teixeira, J.; Matos, S. A.; Arrebola, M.; Costa, J. R.; Felício, J. M.; Fernandes, C. A.; Fonseca, N. J. G. (IEEE Transactions on Antennas and Propagation, 2023)
Mechanical beam steering using a single Transmitarray (TA) can be a cost-effective solution for a high-gain antenna with wide-angle scanning. Elevation scanning can be achieved by a linear displacement of the feed in the focal plane parallel to the aperture of diameter D. When designing compact terminals with a short focal length F and with high gain, the aberrations caused by this mechanical movement become the main limiting factor for the maximum scanning range. This work presents a novel design method for devising the TA phase correction with an even distribution of these aberrations among all beam directions. A significant improvement in the scanning performance is achieved when compared with the conventional single-focus phase correction approach. To validate the proposed approach, we consider a TA design at Ka-band (30 GHz) F/D≅0.34. A multifocal TA design was manufactured using 3D printed unit-cells. To highlight the proposed concept, the antenna configuration is stripped to the bare minimum: a perforated dielectric slab with in-plane mechanical movements in front of an open-ended standard waveguide used as feed. This antenna scans up to 50°, with a gain of 25 dBi at 30 GHz, 2.5 dB of scan loss, SLL <-10 dB and 1dB-bandwidth of 6.7%.